Título Padrão - Oliveira Rocha, Nicole; Teixeira Loures, José Maurício (Revista de Psicologia, 2022)
This article proposes to reflect on the film “They Live” (Carpenter, 1988), by director John Carpenter, considering the formulations of Freud and Lacan on the constitution of the subject and the Lacanian development on the discourse of the capitalist. Carpenter, in his cinematographic work, presents the capitalism from the perspective of the working class that suffers from the effects caused by the system. The aim of this study is to approach, based on psychoanalytic theory in conjunction with cinema, the subject's relation with consumer objects.